Weighted abdominal traction for assistance in abdominal closure - Wendy Jo Svetanoff; C. Jason Smithers; Russell Jennings (Elsevier, 2018)
Introduction: Loss of abdominal domain is an unsolved problem in many complex abdominal procedures. We report three patients who underwent weighted traction and use of retention sutures to prevent fascial retraction. Cases: Our first patient had esophageal metaplasia and a recalcitrant esophageal stricture after having esophageal atresia repair as an infant. Due to vascular congestion of his new conduit, his abdomen was left open. Respiratory compromise was noted on attempted closure, so the patient's abdominal fascia was placed on 20 pounds of traction to prevent fascial retraction. His abdomen was able to be closed after 7 days. Our second patient had a caustic ingestion and underwent a jejunal interposition. Due to the length of the procedure, the abdomen was left open. The fascia was sutured to a silastic silo and placed on 30 pounds of traction. After 8 days, the patient's abdomen was able to be closed primarily. Our third patient presented with persistent aspiration after esophageal atresia repair. Due to concern for her jejunal conduit, her abdomen was left open and placed on weighted traction. Once the abdomen was suitable for closure, an abdominal vac was placed, and continuous fascial tension was applied using #5 Ethibond sutures. Her abdomen was fully closed 10 days later. Discussion: One of the concerns with temporary abdominal closure is retraction of the fascia. We report three cases where the fascia and abdominal wall were placed on weighted traction, which allowed for retention of abdominal domain and delayed primary closure without grafts or mesh. This approach adds to the options available to aid in closure of the complex abdomen.